Limitations of dual time point FDG-PET imaging in the evaluation of focal abdominal lesions - Döbert, N.; Hamscho, N.; Menzel, C.; Neuss, L.; Kovács, A. F.; Grünwald, F. (Nuklearmedizin - NuclearMedicine, 2004)
Aim: For the evaluation of the diagnostic potential of dual time point FDG positron emission tomography (PET) in patients with suspicious focal abdominal up-take, dual time point PET imaging was compared with clinical findings. Patients, methods: In a prospective study, 56 patients exhibiting a solitary suspicious, intense abdominal FDG uptake, underwent dual time point PET imaging for staging or restaging of different malignant tumors, maximal standardized uptake value (SUVmax) measurements included. The first acquisition was started 64.8 ± 19.5, the second 211.3 ± 52.5 min after FDG injection. The final diagnosis based on CT or MRT imaging and a follow-up period of 12.6 ± 2.8 months. Additionally, colonoscopy was done in 6 patients. In another 6 patients histopathology was obtained from CT guided biopsy. Results: Malignant focal abdominal lesions with a SUVmax <2.5 (n = 4) showed an uptake increase of ≥30%. In the remaining malignant cases with an uptake of ≥2.5 (n = 11), up-take increased in 64% and decreased in 36%. Malignant lesions showing FDG uptake decrease (n = 4) had an initial SUVmax value ≥2.5 and remained with a SUVmax ≥2.5 in the second imaging. In benign lesions with an initial SUVmax ≥2.5 (n = 31), the uptake increased in 17 patients (55%) and decreased in 14 patients (45%). All lesions which changed configuration (33%) were confirmed as benign (n = 5). Conclusion: Using dual time point PET abdominal lesions show a very hetergenous uptake pattern regardless of their dignity. Malignancy can only be reliably excluded in lesions which change their configuration and in lesions with an initial SUVmax value <2.5 combined with an SUV decrease in the delayed imaging. Particularly abdominal lesions which show an initial SUVmax ≥2.5 combined with a SUV increase in the delayed imaging are suspicious for malignancy and need further clarification.
Keywords: Dual time point PET imaging; focal abdominal uptake; standardized uptake value (SUV); dignity